1993
DOI: 10.1080/10826079308020913
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Chlordiazepoxide and Selected Chlordiazepoxide Mixtures Using Capillary SFC

Abstract: Journal of Liquid ChromatographyPublication details, including instructions for authors and subscription information: ABSTRACTThe analysis of chlordiazepoxide and selected chlordiazepoxide mixtures using supercritical fluid chromatography (SFC) has been investigated. The separations were carried out on four different stationary phases (SBmethyl-I 00, SB-biphenyl-30, SB-smectic and SB-cyanopropyl-50) with carbon dioxide as the mobile phase and flame ionization detection. The relative retention data obtained usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Peytavin et al reviewed the potential of open-tubular SFC for the determination of polar pharmaceutical actives (244). Jagota and Stewart published a number of evaluations of open-tubular SFC for the determination of particular types of actives: estrogens (245), diazepam, chlordiazepoxide, and related compounds (246,247), and nonsteroidal antiinflammatory agents (248). Of three polysiloxane columns evaluated (100% methyl, 30% biphenyl/70% methyl, and 50% cyanopropyl/50% methyl), the cyanopropyl provided best results for the estrogens and the diazepam-and chlordiazepoxide-related compounds, while greater success was achieved with the biphenyl column for the antiinflammatory compounds.…”
Section: Snyder Et Al Successfully Determined Tocopherols By Both Gcmentioning
confidence: 99%
“…Peytavin et al reviewed the potential of open-tubular SFC for the determination of polar pharmaceutical actives (244). Jagota and Stewart published a number of evaluations of open-tubular SFC for the determination of particular types of actives: estrogens (245), diazepam, chlordiazepoxide, and related compounds (246,247), and nonsteroidal antiinflammatory agents (248). Of three polysiloxane columns evaluated (100% methyl, 30% biphenyl/70% methyl, and 50% cyanopropyl/50% methyl), the cyanopropyl provided best results for the estrogens and the diazepam-and chlordiazepoxide-related compounds, while greater success was achieved with the biphenyl column for the antiinflammatory compounds.…”
Section: Snyder Et Al Successfully Determined Tocopherols By Both Gcmentioning
confidence: 99%
“…By means of modifiers added to the gas, one can effectively program the chromatography without the high temperatures of GC or the solvent use of HPLC (53)(54)(55)(56)(57)(58).…”
Section: Quantitation and Identificationmentioning
confidence: 99%
“…The United States Pharmacopeia (USP) stated the nonaqueous titration method for the assay of clidinium bromide and chlordiazepoxide [ 4 ]. Few methods for the determination of clidinium bromide and chlordiazepoxide in combined dosage forms including HPLC [ 5 7 ], derivative spectrophotometry [ 8 , 9 ], spectrophotometry using multivariate calibration techniques [ 10 ], and capillary SFC [ 11 ] have been reported. Literature survey revealed that some analytical methods have been used for the individual estimation of clidinium bromide and chlordiazepoxide.…”
Section: Introductionmentioning
confidence: 99%